Respon pertumbuhan rumput Setaria (Setaria spachelata) yang diberikan pupuk kotoran satwa Kuskus asal penangkaran - Fredrik R.S. Mauri; Diana Sawen; Alnita Baaka (Jurnal Sains dan Teknologi Peternakan, 2021)
Cuscus is an arboreal animal whose habitat is in the forest with the type of food consumed are fruits, leaf shoots, and agricultural plants. Animal manure can also be used as organic fertilizer for forage plants. This study aims to determine the growth response of Setaria grass (Setaria sphacelata) given a dose of cuscus manure fertilizer with banana and avocado consumption. The study was designed in a CRD with 3 treatments. The treatments were P0 = without fertilizer (100% soil), P1 = 40 g/polybag of cuscus manure with banana consumption, and P2 = 40 g/polybag of cuscus manure with avocado consumption. Planting is done by pols on polybags measuring 30 x 25 cm. The results showed that the highest plant height of Setaria grass was found in P2 with an average of 101.70, then P1 was 101.47 and P0 was 71.16 cm/week. The results were the same for the number of leaves and tillers, P2 showed significantly higher results (P<0.05), followed by P1 and control. The application of organic fertilizer of cuscus manure with the consumption of bananas and avocados can increase the growth of Setaria grass.